2017
DOI: 10.1002/2016jd026200
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the spectral features and electric field changes of multiple return strokes in negative cloud‐to‐ground lightning

Abstract: Using high time‐resolved spectra and simultaneous records of the electric field change of three negative cloud‐to‐ground (CG) lightning flashes with multiple return strokes, the correlations between the total intensity of ionic lines in the spectra and the corresponding amplitude of the initial electric field change, as well as between the total intensity of the spectra and the channel apparent diameter, have been analyzed. The analysis shows the following: (1) The amplitude of the initial electric field chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
4
9
0
Order By: Relevance
“…In this natural process, an original lightning strike is followed by subsequent flashes propagating along the same path, that has moved as a whole with the air mass under the influence of wind. The delay between reilluminations ranges from tens to hundreds of milliseconds [36][37][38][39][40] strikes, comparable with the conductivity lifetime resulting from shockwave-assisted discharges in our experiments.…”
Section: Resultssupporting
confidence: 79%
“…In this natural process, an original lightning strike is followed by subsequent flashes propagating along the same path, that has moved as a whole with the air mass under the influence of wind. The delay between reilluminations ranges from tens to hundreds of milliseconds [36][37][38][39][40] strikes, comparable with the conductivity lifetime resulting from shockwave-assisted discharges in our experiments.…”
Section: Resultssupporting
confidence: 79%
“…Both increase with the increase of channel height. The positive correlation between the total ionic-line intensity in the spectrum and discharge current is confirmed by Wang et al ( , 2017. Moreover, in the high-time-resolved optical observations at different heights of triggered-lightning channels, Carvalho et al (2015) have found that the peak impulse luminosity was roughly proportional to the peak current squared at the channel bottom.…”
Section: Table 1 Parameters Obtained From the Synchronous Electric Fimentioning
confidence: 72%
“…To 250 μs, with the attenuation of the current, the intensity of all spectral lines is greatly reduced. As the ionic line strength is closely related to the discharge current (Wang et al, ; Wang et al, ), it rapidly decreases with the attenuation of the current, while the channel temperature depends on the action integral of the current. The temperature values hinge on the intensity ratio of lines with different excitation energy when it is diagnosed by equations and .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the discharge characteristics of most negative flashes, the total intensity of the spectra of R0 is stronger than that of the subsequent return strokes. The lines from NII with high excitation energy are also strongest in the spectrum of R0, which means that its discharge current is the most intense (Wang et al, ; Wang et al, ).…”
Section: Experiments and Analysismentioning
confidence: 99%
See 1 more Smart Citation